Consolidation of soft clay foundation improved by geosynthetic reinforced granular columns : numerical evaluation - Alkhorshid, Nima Rostami (2021)
Soft clays are problematic soils as they present high compressibility and low shear strength. There are several methods for improving in situ conditions of soft clays. Based on the geotechnical problem’s geometry and characteristics, the in situ conditions may require reinforcement to restrain instability and construction settlements. Granular columns reinforced by geosynthetic material are widely used to reduce settlements of embankments on soft clays. They also accelerate the consolidation rate by reducing the drainage path’s length and increasing the foundation soil’s bearing capacity. In this study, the performance of encased and layered granular columns in soft clay is investigated and discussed. The numerical results show the significance of geosynthetic stiffness and the column length on the embankment settlements. Furthermore, the results show that granular columns may play an important role in dissipating the excess pore water pressures and accelerating the consolidation settlements of embankments on soft clays.